Isolation of Group H Streptococcal Competence Factor - Perry, Dennis (1973)
Competence factor (CF) was purified 600-fold from culture filtrates of competent group H streptococcus, strain Challis, by fractionation on a carboxymethyl-Sephadex column. The preparation did not contain orcinol- or diphenylamine-positive material, and CF activity was destroyed by trypsin. An examination of its chemical composition revealed 10 amino acids, muramic acid, glucosamine, and glucose.